Métricas da paisagem na avaliação da cobertura vegetal em ottobacias do Estado de Goiás, Brasil Central - Ferreira, Alexandre Aires de Freitas (2012)
In the present study aims to compare the current fragmentation into two basins Tocantins- Araguaia and Paraná as the study area using eight ottobacias distributed over these in the state of Goiás, using three metrics (relative area, circularity index and nearest neighbor ) related to the landscape of Savannah. Thus, we measured the fragments of remaining vegetation, agricultural and urban areas in eight ottobacias through images from the Landsat TM + with spatial resolution of 30 m. The images were analyzed using the software SPRING 5.1.7, © ARCGIS allowing these to be cut, segmented, fragmented, classified and reclassified. Subsequently, the generated images allowed the measurement, using the program FRAGSTATS 3.3, the three landscape metrics for each fragment of each ottobacia. Then, the collected data were subjected to analysis of variance (ANOVA) main effects targeting the comparison between the basins sampled. The results indicate that the vegetation is fragmented in eight ottobacias considered, with a predominance of small fragments with close circles and forms with low average distance between the fragment and another of the same class regardless of the location factor in the Paraná Basin and the Tocantins-Araguaia. These results are attributed to human action and do not contribute to the maintenance of biodiversity.